Carrying the Burden Into the Pandemic – Effects of Social Disparities on Elementary Students’ Parents’ Perception of Supporting Abilities and Emotional Stress During the COVID-19 Lockdown - Vogelbacher, Markus; Attig, Manja (Frontiers in Psychology, 2022)
The COVID-19 pandemic has posed many challenges, especially for families. Both the public and the scientific community are currently discussing the extent to which school closings have worsened existing social differences, especially with regard to children’s academic and socio-emotional development. At the same time, parents have had to manage childcare and home schooling alongside their jobs and personal burdens posed by the pandemic. Parents’ possibilities for meeting these cognitive and emotional challenges might also depend on the different conditions in families. For this reason, the present paper investigates the structural and process characteristics of the family as well as children’s and parents’ psychological characteristics that predict how parents assess their ability to support their child’s learning during homeschooling as well as parents’ perceived emotional stress caused by school closure. The study analyses data of the Newborn Cohort Study of the German National Educational Panel Study. The two dependent variables (self-assessment of abilities, perceived stress) were measured during the COVID-19 pandemic after the first school closure in Germany, at a time when the children of this cohort were attending second grade. Besides a number of control variables (including the child’s struggle with home schooling), families’ structural characteristics (socioeconomic status, education), process characteristics (home learning environment), parents’ psychological characteristics (preceding psychological stress), and the child’s psychological characteristics (self-regulation, school-related independence) from earlier waves were included as predictors. The results of structural equation models show that perceived stress was associated with structural factors and the preceding psychological stress of parents. Parents with higher preceding stress reported higher perceived stress. Interestingly, higher-educated parents also reported more stress than lower educated parents during the pandemic. The effect was the other way around for socioeconomic status – parents with lower socioeconomic status reported more stress than parents with higher socioeconomic status. The self-reported abilities to support the learning of the child seemed to be mainly predicted by the parent’s education as well as preceding psychological stress. To sum up, the results identify important aspects that determine how parents handle the challenges of the school closures. Especially, socially disadvantaged families carry their burden into the pandemic.